Labor and Love: Wives' Employment and Divorce Risk in its Socio-political Context - Lynn P. Cooke; Jani Erola; Marie Evertsson; Michael Gähler; Juho Härkönen; Belinda Hewitt; Marika Jalovaara; Man-Yee Kan; Torkild Hovde Lyngstad; Letizia Mencarini; Jean-Francois Mignot; Dimitri Mortelmans; et al. (Social Politics, 2013)
We theorize how social policy affects marital stability vis-à-vis macro and micro effects of wives' employment on divorce risk in 11 Western countries. Correlations among 1990s aggregate data on marriage, divorce, and wives' employment rates, along with attitudinal and social policy information, seem to support specialization hypotheses that divorce rates are higher where more wives are employed and where policies support that employment. This is an ecological fallacy, however, because of the nature of the changes in specific countries. At the micro level, we harmonize national longitudinal data on the most recent cohort of wives marrying for the first time and find that the stabilizing effects of a gendered division of labor have ebbed. In the United States with its lack of policy support, a wife's employment still significantly increases the risk of divorce. A wife's employment has no significant effect on divorce risk in Australia, Flanders, France, Germany, Italy, the Netherlands, and the United Kingdom. In Finland, Norway, and Sweden, wives' employment predicts a significantly lower risk of divorce when compared with wives who are out of the labor force. The results indicate that greater policy support for equality reduces and may even reverse the relative divorce risk associated with a wife's employment.
Additional information: This is a pre-copy-editing, author-produced PDF of an article accepted for publication in Social Policy following peer review. The definitive publisher-authenticated version "Labor and Love: Wives' Employment and Divorce Risk in Its Socio-political Context / Lynn Prince Cooke, Jani Erola, Marie Evertsson, Michael Gähler, Juho Härkönen, Belinda Hewitt, Marika Jalovaara, Man-Yee Kan, Torkild Hovde Lyngstad, Letizia Mencarini, Jean-Francois Mignot, Dimitri Mortelmans, Anne-Rigt Poortman, Christian Schmitt, Heike Trappe. In: Social Politics 20 (2013), 4, pp. 482-509" is available online at: http://dx.doi.org/10.1093/sp/jxt016
Keywords: 330; Frauenerwerbstätigkeit; Familienstand; Vergleich